Use of Digital Marketing in Marketing of Data and Information Services in Asia - Sanusi, Anwar; Roy Purwanto, Muhammad; Suardi Wekke, Ismail; Utu, La; E. , Laxmi Lydia (International Journal of Psychosocial Rehabilitation, 2020)
Over the past three decades, merchandising has had to remain up and subsume leaps in technology and our reference to it ever since. Whereas the Sales Era witnessed the invention of the phone, swiftly followed by the rise of TV and also the merchandising Department Era. The trade evolution of the merchandising Company Era saw the most important modification among the history of marketing: the first commerce. However, what do these developments mean for the long term of merchandising? Our new Digital Skills report found that loads of selling professionals unit unsure of their future and believe that digital promoting area unit planning to be necessary to their organization over sequent two years. Despite this once marketers were asked relating to their roles in thirty years’ time, sixty eight among the USA and sixty one among of the nice kingdom and European country believe that their current digital role can while not a ball, it’s inconceivable to ascertain what the long term holds, but to seem forward, we wish to seem back. Here, we tend to look at the 3 major technological developments that have changed the strategy we tend to look at marketing: the net, large data and Smartphone and predict but, they will set the scene for the long term.